Intrahospital infections in the medical student: Infecciones intrahospitalarias en el estudiante de medicina. - Loayza-Castro, Joan A. (2020)
The diseases associated with care in the health sector is a problem that not only involves patients who enter the service, but also the staff and students who carry out their practices in the different institutions. In-hospital infections are defined as: "Localized or systemic diseases resulting from an adverse reaction resulting from exposure to an infectious agent or its toxins, with no evidence that the infection was present or in the incubation period at the time of care." The lack of knowledge on the part of the personnel and students of the health sciences that are in contact with the patients, in addition to the realization of sanitary practices without taking into account the pertinent biosecurity measures are the main reasons for contracting a nosocomial infection.